Architecture and synthesis of P,N-heterocyclic phosphine ligands - Munzeiwa, Wisdom A.; Omondi, Bernard; Nyamori, Vincent O. (Beilstein Journal of Organic Chemistry, 2020)
Diverse P,N-phosphine ligands reported to date have performed exceptionally well as auxiliary ligands in organometallic catalysis. Phosphines bearing 2-pyridyl moieties prominently feature in literature as compared to phosphines with five-membered N-heterocycles. This discussion seeks to paint a broad picture and consolidate different synthetic protocols and techniques for N-heterocyclic phosphine motifs. The introduction provides an account of P,N-phosphine ligands, and their structural and coordination benefits from combining heteroatoms with different basicity in one ligand. The body discusses the synthetic protocols which focus on P–C, P–N-bond formation, substrate and nucleophile types and different N-heterocycle construction strategies. Selected references are given in relation to the applications of the ligands.
Keywords: ligand synthesis; P,N-heterocyclic phosphines